EFEKTIFITAS PENGEMBANGAN PERANGKAT PEMBELAJARAN BERVISI ?óÔé¼?ØREST?óÔé¼?Ø (RELIGION, ENVIRONMENT, SCIENCE, AND TECHNOLOGY) DAN BERPENDEKATAN BIOENTREPRENEURSHIP TERHADAP PRESTASI BELAJAR MAHASISWA BIOLOGI - Eko Retno Mulyaningrum (Bioma : Jurnal Ilmiah Biologi, 2014)
THE EFFECTIVENESS OF DEVELOPING REST (RELIGION, ENVIRONMENT, SOCIETY, TECHNOLOGY) LESSON PLAN AND BIOENTREPRENEURSHIP APPROACH TO THE BIOLOGY STUDENTS?óÔé¼Ôäó LEARNING OUTCOME ABSTRACT The aim of this study was to develop an instructional instrument for Biology based on Religion, Environment, Society, and Technology (REST). It employed a bioentrepreneurship approach, discribed students?óÔé¼Ôäó learning outcome while they attending in the subject of enviromental pollutions, which was a part of the enviromental science. The subjects for this research were the second semester students at PGRI Semarang University, Biology Education Department. This research used a Research & Development method. The learning outcomes of the subjects in the experimental group on the materials given were higher than those in the control group. The REST-based instructional instrument, helped by the bioentrepreneurship approach, consisted of lesson plan, lectured contracts, modules,?é?á students?óÔé¼Ôäó work sheets, and instrument evaluation could be applied for pollution material, subject of environmental knowledge. ?é?á Keywords: Instructional instrument, REST (Religion, Environment, Science and Technology), Bioentrepreneurship, Environmental Knowledge. ?é?á ABSTRAK Tujuan dari penelitian ini adalah untuk mengembangkan dan menguji efektivitas produk perangkat pembelajaran terhadap prestasi belajar mahasiswa melalui pembelajaran bervisi REST (Religion, Environment, Science, and Technology). Penelitian ini menggunakan pendekatan Bioentrepreneurship untuk mengetahui hasil pembelajaran mahasiswa dalam materi pencemaran lingkungan pada perkuliahan Pengetahuan Lingkungan. Subjek penelitian ini adalah mahasiswa semester II Jurusan Pendidikan Biologi Universitas PGRI Semarang. Metode penelitiannya menggunakan Research & Development. Hasil pembelajaran di kelompok eksperimen lebih tinggi dibandingkan dengan kelompok kontrol. Kesimpulannya adalah bahwa perangkat pembelajaran berbasis REST dan berpendekatan bioentrepreneurship, terdiri dari rencana pembelajaran, bahan ajar, lembar kegiatan mahasiswa, dan soal evaluasi efektif untuk digunakan pada perkuliahan Pengetahuan Lingkungan materi Pencemaran Lingkungan. ?é?á Kata kunci: Perangkat pembelajaran, REST (Religion, Environment, Science and Technology), Bioentrepreneurship, Pengetahuan Lingkungan